Get there early to photograph bats pollinating flowers in the field - Domingos Melo, Arthur (2021)
We present, for the first time, the spectral reflectance curves of bat-pollinated flowers using as model Ceiba glaziovii (Malvaceae), an impressive tree whose crown turns completely white during the reproductive season, and 13 other chiropterophilous species from Caatinga dry forest, Northeastern Brazil. Flowers from most species reflect light in the blue, green, and red ranges (white to humans). Contrary to what has been widely disseminated, there was little reflection in the ultraviolet range. From these data, we hypothesized how nectarivorous bats, which often begin foraging before sunset, would use color as a clue in their search for flowers freshly opened.